The Recognition of the Other as a Real Freedom in Fichtean Political Thought - Arrese Igor, Héctor Oscar (ENDOXA, 2019)
This paper aims to show that the Fichtean theory of recognition of the other carries important consequences that are relevant to the theory of property. Fichte intimately links the ideas of freedom and property as the basic means for subsistence. In order to show this link, the deduction of property is reconstructed from the principle of law. Furthermore, he develops an idea of a social division of labor centrally planned by the state. Finally, the paper includes the relationships established between the Fichtean idea of a right to subsistence, and the debate about formal freedom and real freedom.